Evaluation of Rhizobacterial Isolates Antagonism to Meloidogyne incognita Infecting Tomato - Devindrappa, M.; Kamra, A. (University of Jaffna, 2022)
Tomato is one of the most widely cultivated vegetable in the tropical and subtropical regions of the world. Root-knot nematode (RKN) species, Meloidogyne incognita and M. javanica are serious constraints to vegetable crops, especially tomato under protected cultivation, causing yield loss up to 25-100%. In the present study rhizobacterial isolates from polyhouse tomato cultivars were isolated and assessed for M. incognita antagonism. Among 80 isolates that were tested for mortality of M. incognita juveniles (J2s). The results show that cell free filtrate (CFF) of four rhizobacterial isolates (B. pumilus, B. megaterium, B. cereus and B subtilis) caused high mortality (>90%) in M. incognita J2s on exposure at 24h. Egg masses kept in CFF showed significant (p< 0.05) hatch inhibition in the range of 85.04 to 100% compared to control, on incubation for 21 days. Among the treatments, B. subtilis caused maximum inhibition (88.6-100 %) followed by B. pumilus (83-100%), B. cereus (81.5-94.7%), and B. megaterium (78.83-90.7%) as compared to control. Pluronic gel bioassays using tomato seedlings (cv Pusa Ruby) revealed that significantly reduced (p <0.05) juvenile (J2s) attraction towards the rhizobacteria treated roots on observation at 2h and 4h.The maximum inhibition was observed with B. subtilis treatment where an average numbers of J2s that reached a distance of 0.5-1.0 cm were 15-20 at 2h in treated plates as compared 29 -30 in control treatment.. The rhizobacterial isolates were significantly (p <0.05) reduced nematode infection Thus the rhizobacterial isolates were antagonistic to M. incognita in tomato. Their utilization in polyhouses is a promising approach for management of M. incognita in tomato.
Keywords: Bacillus pumilus; Rhizobacteria; Egg hatch inhibition; Meloidogyne incognita; Tomato